2015
DOI: 10.1016/j.eplepsyres.2014.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal differences in the c-fos pathway between C57BL/6J and DBA/2J mice following flurothyl-induced seizures: A dissociation of hippocampal Fos from seizure activity

Abstract: Significant differences in seizure characteristics between inbred mouse strains highlight the importance of genetic predisposition to epilepsy. Here, we examined the genetic differences between the seizure-resistant C57BL/6J (B6) mouse strain and the seizure-susceptible DBA/2J (D2) strain in the phospho-Erk and Fos pathways to examine seizure-induced neuronal activity to uncover potential mechanistic correlates to these disparate seizure responsivities. Expression of neural activity markers was examined follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…For determination of forebrain and brainstem seizure thresholds throughout the repeated‐flurothyl paradigm, a second group of male mice (C57BL/6J [n = 24] and DBA/2J [n = 24]) were utilized, and their generalized forebrain and brainstem seizure thresholds were determined at three time points in the repeated‐flurothyl model: after one or eight flurothyl induction trials, or following eight flurothyl seizures, 28‐day incubation, and final flurothyl rechallenge (n = 8/time‐point/strain). Mice were ~8 weeks old when seizure testing began, consistent with previous studies utilizing the repeated‐flurothyl model …”
Section: Methodssupporting
confidence: 63%
See 2 more Smart Citations
“…For determination of forebrain and brainstem seizure thresholds throughout the repeated‐flurothyl paradigm, a second group of male mice (C57BL/6J [n = 24] and DBA/2J [n = 24]) were utilized, and their generalized forebrain and brainstem seizure thresholds were determined at three time points in the repeated‐flurothyl model: after one or eight flurothyl induction trials, or following eight flurothyl seizures, 28‐day incubation, and final flurothyl rechallenge (n = 8/time‐point/strain). Mice were ~8 weeks old when seizure testing began, consistent with previous studies utilizing the repeated‐flurothyl model …”
Section: Methodssupporting
confidence: 63%
“…Previously, we have shown that the ventromedial nucleus of hypothalamus (VMH) displays increased bilateral neuronal activity, as determined by Fos immunolabeling, in C57BL/6J mice having forebrain→brainstem seizures . Functionally, bilateral ibotenic acid lesions of the VMH are able to block the expression of the brainstem seizure component of forebrain→brainstem seizures .…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Studies are currently underway attempting to elucidate what these genetic differences could be and the signaling pathways that may be involved. Last, gene expression changes have been observed in C57BL/6J mice over the course of the flurothyl induction period (Kadiyala et al, 2015), which could indicate the possibility of flurothyl-induced and/or seizure-induced changes in gene expression contributing to the transient nature of spontaneous seizures in C57BL/6J mice. Genes that were shown to change with flurothyl-induced seizures were similar to what has been observed in electrical kindling models (Christensen et al, 2010;Kadiyala et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Following a one month incubation period and a rechallenge with flurothyl, C57BL/6J mice express a clonic-forebrain seizure that rapidly and uninterruptedly transitions into a tonic-brainstem seizure (Samoriski and Applegate, 1997; Ferland and Applegate, 1998b). We refer to these seizures as forebrain→brainstem seizures denoting the ictal progression from the forebrain seizure network to the brainstem seizure network (Papandrea et al ., 2009; Kadiyala et al ., 2015). Lastly, C57BL6/J mice exposed to the repeated flurothyl seizure model rapidly develop spontaneous seizures that appear to remit without treatment following 1 month (Kadiyala et al ., 2016), in contrast to DBA2/J mice which also rapidly develop spontaneous seizures that do not remit (Kadiyala and Ferland, 2017).…”
Section: Introductionmentioning
confidence: 99%